2022
DOI: 10.3389/fnmol.2021.751570
|View full text |Cite
|
Sign up to set email alerts
|

Netrin-1 Ameliorates Postoperative Delirium-Like Behavior in Aged Mice by Suppressing Neuroinflammation and Restoring Impaired Blood-Brain Barrier Permeability

Abstract: Postoperative delirium (POD) is a common and serious postoperative complication in elderly patients, and its underlying mechanism is elusive and without effective therapy at present. In recent years, the neuroinflammatory hypothesis has been developed in the pathogenesis of POD, in which the damaged blood-brain barrier (BBB) plays an important role. Netrin-1 (NTN-1), an axonal guidance molecule, has been reported to have strong inflammatory regulatory and neuroprotective effects. We applied NTN-1 (45 μg/kg) to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 67 publications
1
13
0
Order By: Relevance
“…[23] Disruption of the BBB is thought to cause neuroinflammation. [24] According to a murine tibial fracture surgery model, activation of T cells increases the levels of IL-17A, and disruption of the BBB is thought to be associated with POD-like behavior. [25] Sometimes, the body has a systemic inflammatory response such as sepsis.…”
Section: Resultsmentioning
confidence: 99%
“…[23] Disruption of the BBB is thought to cause neuroinflammation. [24] According to a murine tibial fracture surgery model, activation of T cells increases the levels of IL-17A, and disruption of the BBB is thought to be associated with POD-like behavior. [25] Sometimes, the body has a systemic inflammatory response such as sepsis.…”
Section: Resultsmentioning
confidence: 99%
“…IL-6 has been found to be a significant predictor of POD in various surgical conditions (elective surgery or emergency) ( Adamis et al, 2021 ). It has also been shown that decreasing the expression of IL-6 and upregulating the expression of IL-10 in the peripheral blood, hippocampus, and prefrontal cortex reduces microglia activation and reduces delirium-like behavior in mice ( Li et al, 2022b ).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, our results are similar to results from animal models of perioperative neurocognitive disorders, in which postoperative blood-brain barrier dysfunction has been demonstrated following orthopedic surgery and has been associated with delirium-like behavioral changes. [33][34][35] Indeed, in mice these delirium-like behavioral changes are prevented when blood-brain barrier dysfunction is reduced with administration of netrin-1, a protein that upregulates endothelial tight junction production to support blood-brain barrier integrity 36 Two other lines of evidence also suggest that it is biologically plausible for blood-brain barrier dysfunction to play an etiologic role in delirium. First, a leaky blood-brain barrier can allow both peripheral inflammatory molecules and leukocytes to enter the brain, 12,37 both of which have been shown to result in cognitive dysfunction in both animal models and other human disorders ranging from multiple sclerosis to major depression.…”
Section: Discussionmentioning
confidence: 99%